Cytokine-Neuroantigen Fusion Proteins as a New Class of Tolerogenic, Therapeutic Vaccines for Treatment of Inflammatory Demyelinating Disease in Rodent Models of Multiple Sclerosis - Mannie, Mark D.; Blanchfield, J. L.; Islam, S. M. Touhidul; Abbott, Derek J. (Frontiers in Immunology, 2012)
Myelin-specific induction of tolerance represents a promising means to modify the course of autoimmune inflammatory demyelinating diseases such as multiple sclerosis (MS). Our laboratory has focused on a novel preclinical strategy for the induction of tolerance to the major encephalitogenic epitopes of myelin that cause experimental autoimmune encephalomyelitis (EAE) in rats and mice. This novel approach is based on the use of cytokine-NAg (neuroantigen) fusion proteins comprised of the native cytokine fused either with or without a linker to a NAg domain. Several single-chain cytokine-NAg fusion proteins were tested including GMCSF-NAg, IFNbeta-NAg, NAgIL16, and IL2-NAg. These cytokine-NAg vaccines were tolerogenic, therapeutic vaccines that had tolerogenic activity when given as pre-treatments before encephalitogenic immunization and also were effective as therapeutic interventions during the effector phase of EAE. The rank order of inhibitory activity was: GMCSF-NAg, IFNbeta-NAg > NAgIL16 > IL2-NAg > MCSF-NAg, IL4-NAg, IL13-NAg, IL1RA-NAg, and NAg. Several cytokine-NAg fusion proteins exhibited antigen-targeting activity. High affinity binding of the cytokine domain to specific-cytokine receptors on particular subsets of APC resulted in the concentrated uptake of the NAg domain by those APC which in turn facilitated the enhanced processing and presentation of the NAg domain on cell surface MHC class II (MHCII) glycoproteins. For most cytokine-NAg vaccines, the covalent linkage of the cytokine domain and NAg domain was required for inhibition of EAE, thereby indicating that antigenic targeting of the NAg domain to APC was also required in vivo for tolerogenic activity. Overall, these studies introduced a new concept of cytokine-NAg fusion proteins as a means to induce tolerance and to inhibit the effector phase of autoimmune disease. The approach has broad application for suppressive vaccination as a therapy for autoimmune diseases such as MS.